O processo de fechamento das escolas no campo em Itapejara D' Oeste/PR: o caso da Escola Estadual de Lageado Bonito e do Colégio Estadual do Campo Carlos Gomes - Mazur, Ivania Piva (2016)
The research analyzed the closing process and closing attempts of schools in the field with the offer of the final years of Primary Education in the countryside in Itapejara D Oeste, Southwest region of Paraná State. The general objective was to analyze this process, as well as showing the resistances and challenges for school in the field. The specific objectives proposed were to identify the changes in the Brazilian countryside since 1950 and its determinations on the reduction of the rural population; contextualize and differentiate the concepts of rural education and field education on the national scene; understand the school closure processes in the rural area in the national and local context, describe the process of implementation and subsequent stop of offering final years/grades of Primary Education in the countryside from a closure and completion case and from a closing way case. From a qualitative approach in the perspective of historical-dialectical materialism, there was a case study, with the use of procedures semi structured interviews and documental analysis. It approached the changes occurred in the Brazilian countryside, due to the capitalism, as well as its effects that culminated in the reduction of rural population and consequently the reduction of enrollment of the schools in the countryside. It also addressed the rural education and rural school and, as a counterpoint, the Field Education in order to analyze the process of closing of these schools later on. The research showed that the offer of Primary Education in the countryside of Itapejara D Oeste both for early years as the final years was precarious and insufficient, proving the negligence of the authorities to the education of the rural population. The analysis of the implementation process, closing and attempts to the closing of the schools showed that the offer of the final years of Elementary School was not the result of a public policy designed in order to attend the country population, but the result of claims and mobilization of the communities, which in the same way resisted in face of attempts to close schools. The practice of closing schools was based in economic-quantitative justification, disregarding cultural aspects that are present in the issue of closing schools in the countryside. In short, the research reflects the great historical debt to the education of the countryside people, noting that it is not enough public educational policies. These should be linked to other public policies that guarantee better life expectancies in the country so that families want and can stay there.